The Role of the Bestee Program Facilitators in Improving BTPN Syariah Customer Product Marketing Through Educational Strategies and Digital Practices : Peran Fasilitator Pendamping Program Bestee Dalam Meningkatkan Pemasaran Produk Nasabah BTPN Syariah Melalui Strategi Edukasi Dan Praktik Digital - Zakiyyah Adinda Berliana; Daisy Marthina Rosyanti (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
MSMEs (Micro, Small, and Medium Enterprises) play an important role in the Indonesian economy, but still face major challenges in terms of product marketing. Limited knowledge of marketing strategies, minimal use of digital technology, and lack of ability to create promotional content are common obstacles experienced by business actors, especially among the productive underprivileged. This community service activity aims to increase the marketing capacity of MSME customers through mentoring by BTPN Syariah facilitators in the Bestee program. The program is implemented in Wonocolo District, Surabaya, with an educational and participatory approach. The methods used include needs assessment, marketing material education, direct practice in making promotional tools, and evaluation of activity results. Participants consisted of 10 customers who were mentored for 4 months through weekly meetings. The results of the activity showed a significant increase in participants' understanding of conventional and digital marketing, as well as progress in skills in using social media, product packaging, and promotion management. Facilitators also play an important role in building participants' motivation and self-confidence, thus having a positive impact on their business competitiveness. This activity proves that structured and sustainable mentoring can be a concrete solution in community-based economic empowerment. Therefore, the role of facilitators must continue to be strengthened so that MSMEs can develop sustainably and adaptively to market changes.